Effects of High-Intensity Interval Training on Selected Adipokines and Cardiometabolic Risk Markers in Normal-Weight and Overweight/Obese Young Males—A Pre-Post Test Trial - Nejmeddine Ouerghi; Mohamed Kacem Ben Fradj; Martine Duclos; Anissa Bouassida; Moncef Feki; Katja Weiss; Beat Knechtle (Biology, 2022)
The study aimed to assess effects of high-intensity interval training (HIIT) on plasma adipokines and cardiometabolic markers in normal and excess weight youth. Eighteen healthy young males (18.2 ± 1.06 yrs.) were divided in normal-weight group (NWG; body mass index (BMI), 20.5 ± 1.51 kg/m2; n = 9) and excess-weight group (EWG; BMI, 30.8 ± 4.56 kg/m2; n = 9). Participants performed an eight-week HIIT program without caloric restriction. Body composition, plasma leptin, adiponectin, chemerin, omentin-1, lipids, C-reactive protein (CRP), and the homeostasis model assessment index for insulin resistance (HOMA-IR) were assessed before and after the HIIT program. The program resulted in significant increases in omentin levels (p < 0.01) in EWG (27%) and NWG (22%), but no changes in leptin, adiponectin, and chemerin in both groups. BMI (−1.62%; p = 0.015), body fat (−1.59%; p = 0.021), total cholesterol (−11.8%; p = 0.026), triglycerides (−21.3%; p = 0.023), and HOMA-IR (−31.5%; p = 0.043) decreased in EWG only. Repeated measures detected significant interaction “Time x Group” for body mass and BMI only. Eight-week HIIT program improved body composition, lipid profile, and insulin sensitivity in excess-weight individuals. It resulted in an increase in omentin levels in both normal- and excess-weight groups, but no changes in leptin, adiponectin, and chemerin. Body composition has not influenced the response of the four adipokines to HIIT.